Clinical Impact and Economic Burden of Hospital-Acquired Conditions Following Common Surgical Procedures. Issue 22 (15th November 2018) - Horn, Samantha R.; Liu, Tiffany C.; Horowitz, Jason A.; Oh, Cheongeun; Bortz, Cole A.; Segreto, Frank A.; Vasquez-Montes, Dennis; Steinmetz, Leah M.; Deflorimonte, Chloe; Vira, Shaleen; Diebo, Bassel G.; Neuman, Brian J.; et al.
Abstract : Study Design: Retrospective review of prospectively collected data. Objective: To assess the clinical impact and economic burden of the three most common hospital-acquired conditions (HACs) that occur within 30-day postoperatively for all spine surgeries and to compare these rates with other common surgical procedures. Summary of Background Data: HACs are part of a non-payment policy by the Centers for Medicare and Medicaid Services and thus prompt hospitals to improve patient outcomes and safety. Methods: Patients more than 18 years who underwent elective spine surgery were identified in American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database from 2005 to 2013. Primary outcomes were cost associated with the occurrence of three most common HACs. Cost associated with HAC occurrence derived from the PearlDiver database. Results: Ninety thousand five hundred fifty one elective spine surgery patients were identified, where 3021 (3.3%) developed at least one HAC. Surgical site infection (SSI) was the most common HAC (1.4%), then urinary tract infection (UTI) (1.3%) and venous thromboembolism (VTE) (0.8%). Length of stay (LOS) was longer for patients who experienced a HAC (5.1 vs. 3.2 d, P < 0.001). When adjusted for age, sex, and Charlson Comorbidity Index, LOS was 1.48 ± 0.04 days longer ( P < 0.001) and payments were 8893 ± 148 greater ( P < 0.001) for patients with at least one HAC. With the exception of craniotomy, patients undergoing common procedures with HAC had increased LOS and higher payments ( P < 0.001). Adjusted additional LOS was 0.44 ± 0.02 and 0.38 ± 0.03 days for total knee arthroplasty and total hip arthroplasty, and payments were 1974 and 1882 greater. HACs following hip fracture repair were associated with 1.30 ± 0.11 days LOS and 4842 in payments ( P < 0.001). Compared with elective spine surgery, only bariatric and cardiothoracic surgery demonstrated greater adjusted additional payments for patients with at least one HAC (9975 and 10, 868, respectively). Conclusion: HACs in elective spine surgery are associated with a substantial cost burden to the health care system. When adjusted for demographic factors and comorbidities, average LOS is 1.48 days longer and episode payments are 8893 greater for patients who experience at least one HAC compared with those who do not. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text